Evaluating the risk of post-operative abscess formation following use of hemostatic agents at time of hysterectomy - Megan Howard; Jeanine N. Staples; Samhita Nelamangala; Connell Kling; Linda R. Duska (Elsevier, 2022)
Objective: At an academic institution in rural Virginia, we noticed a trend of increased re-admissions for postoperative pelvic abscesses. The primary study objective was to determine if intraoperative use of hemostatic agents (HA) was associated with postoperative abscess formation in patients undergoing hysterectomy. Methods: Retrospective chart review identified women who underwent hysterectomy by a Gynecologic Oncologist for any indication at a single institution from January 1, 2019 through December 31, 2019. Patient and surgical characteristics were abstracted and comparisons were made among those who received any HA and those that did not. The relationship between intraoperative HA use and postoperative pelvic abscess formation was determined using multivariate logistic regression. Secondary outcomes evaluated included the presence of other major post-operative adverse events. Results: 428 hysterectomies were identified with a postoperative pelvic abscess rate of 3.7 %. Abscesses were identified in 4 (2.2 %) of cases without vs 12 (4.9 %) of cases with HA use with a logistic regression model demonstrating no significant difference in the groups (OR = 2.10, p = 0.22). Data showed an increase in presentation to the Emergency Department (ED) (OR = 3.43, p = 0.002 adjusted) and higher odds of readmission within 30 days of surgery (OR = 3.19, p = 0.03) with HA use. Conclusions: No association was found between HA use and abscess formation; however, data showed HA use was associated with increased odds of presentation to the ED and readmission to the hospital within 30 days of surgery. Given the potential negative impact on patient outcomes, use of these products at time of hysterectomy should be made with careful consideration.